Tandem arylation and regioselective allylic etherification of 2, 3-allenol via Pd/B cooperative catalysis. Issue 35 (28th August 2019) - Li, Hongfang; Li, Tao; Hsueh, Yu Jen; Wu, Xue; Xu, Feng; Zhang, Yong Jian
Abstract : An efficient method for the construction of arylated allylic ethers was developed via three-component tandem arylation and allylic etherification of 2, 3-allenol with aryl iodides and alcohols. Abstract : An efficient method for the construction of arylated allylic ethers was developed via three-component tandem arylation and allylic etherification of 2, 3-allenol with aryl iodides and alcohols. In the cooperative catalytic system of a palladium complex and triethylborane, the process allows rapid access to functionalized 1-arylvinylated 1, 2-diol derivatives in good to high yields with complete branch-selectivities. The synthetic utility of the present process was demonstrated by the late-stage functionalization of a drug molecule, the gram-scale synthesis and the elaboration of the products.